Pengaruh Blended Learning DLPCA Models Terhadap Kemampuan Numerasi Siswa - Ma'rifah, Sila Nur; Kuswandi, Dedi; Soepriyanto, Yerry (Universitas Negeri Malang, 2023)
In the Basic Programming subject, it contains numeracy skills. Meanwhile the 2018 PISA results stated that students' numeracy skills were weak. Basic Programming itself is a mandatory prerequisite material for vocational high school students which is quite difficult but very important to master. The application of Blended Learning DLPCA Models (BL-DLPCA Models) learning strategies is carried out to get the combined advantages of online learning and face-to-face learning. BL-DLPCA Models have a syntax namely Discover, Learn, Practice, Collaborate and Asses which aims to integrate instructors, students and are ready to use technology to meet challenges in learning. The use of BL-DLPCA Models learning strategies aims to improve students' numeracy skills in Basic Programming subjects. Quasi-experiment quantitative research design type pottest only control group design. The experimental group applied the BL-DLPCA Models and the both control group applied online and face-to-face learning strategies respectively. The results of the study stated that the use of BL-DLPCA Models learning strategies had a better effect on students' numeracy abilities in Basic Programming subjects compared to online and face-to-face learning strategies.AbstrakDidalam mata pelajaran Pemrograman Dasar memuat kemampuan numerasi. Sementara itu hasil PISA 2018 yang menyatakan bahwa lemahnya kemampuan numerasi siswa. Pemrograman Dasar sendiri merupakan materi wajib prasyarat siswa sekolah menengah kejuruan yang cukup sulit tetapi sangat penting untuk dapat dikuasai. Penerapan strategi pembelajaran Blended Learning DLPCA Models (BL-DLPCA Models) dilakukan untuk mendapatkan gabungan keuntungan dari pembelajaran online dan pembelajaran tatap muka. BL-DLPCA Models memiliki syntax yaitu Menemukan (Discover), Mempelajari (Learn), Berlatih (Practice), Berkolaborasi (Collaborate) dan Dinilai (Asses) bertujuan mengintergasikan instruktur, siswa dan siap menggunakan teknologi untuk memenuhi tantangan dalam pembelajaran. Penggunaan strategi pembelajaran BL-DLPCA Models bertujuan untuk meningkatkan kemampuan numerasi siswa pada mata pelajaran Pemrograman Dasar. Penelitian kuantitatif quasi-eksperiment design tipe pottest only control group design. Pada kelompok eksperimen menerapkan BL-DLPCA Models dan dua kelompok kontrol lain masing-masing menerapkan pembelajaran online dan pembelajaran tatap muka. Hasil penelitian menyatakan bahwa penggunaan strategi pembelajaran BL-DLPCA Models memberikan pengaruh terhadap kemampuan numerasi siswa pada mata pelajaran Pemrograman Dasar lebih baik dibanding dengan strategi pembelajaran online maupun tatap muka.